Effects of donor position and multiple charge transfer pathways in asymmetric pyridyl-sulfonyl TADF emitters. (June 2022) - Haykir, Gulcin; Aydemir, Murat; Tekin, Adem; Tekin, Emine; Danos, Andrew; Yuksel, Fatma; Hizal, Gurkan; Monkman, Andrew P.; Turksoy, Figen
Abstract: We have designed and synthesized a pair of highly asymmetric D -aA-D′ type pyridyl-sulfonyl based isomers comprising phenothiazine (PTZ) and carbazole (Cz) donor units, which are able to emit thermally activated delayed fluorescence. PTZ- p S4-Py-2Cz and PTZ- m S4-Py-2Cz both possess spatial separation of HOMO/LUMO on the donor and acceptor moieties, resulting in small calculated singlet–triplet energy gaps ( 0.25 eV). Both isomers exhibit dual emission, which is attributed to charge transfer states associated with the Cz and PTZ moieties at higher and lower energies, respectively. Photoluminescence quantum yields and time-resolved emission decays show significant differences for the two isomers, with the para- isomer exhibiting more efficient emission and stronger delayed fluorescence than the meta- isomer – in strong contrast to recently reported analogous Cz-Cz D -aA-D isomers. The findings clearly show that the interconversion of triplets via the rISC mechanism is promoted when parallel Cz and PTZ charge transfer states are allowed to interact, explaining the improved performance of the Cz-PTZ materials compared to the previous Cz-Cz ones. Finally, moderate device performance was achieved in warm-yellowish (CIE; 0.41; 0.53 & 0.49; 0.48) non-doped OLEDs, which exhibited 0.5% & 1.9% maximum external quantum efficiencies for the meta- and para- isomers, respectively. Graphical Abstract: ga1 Highlights: We report the synthesis and structural characterization of D -aA-D′ type pyridyl-sulfonyl based isomers, which are able to emit thermally activated delayed fluorescence. The isomer with para- phenothiazine group displays significantly improved delayed fluorescence and emission quantum yields. Both materials exhibit warm-yellowish emission in non-doped OLEDs with CIE coordinates of (0.41; 0.53, 0.49; 0.48) and maximum EQEs of 0.5% ( meta- isomer) and 1.9% ( para- isomer).